Association of Body Mass Index and Metabolic Health Status With Cerebrovascular Diseases in 617 755 Chinese Older People - Lirong Dong; Yuanyuan Wang; Dakang Ji; Zhengkai Shen; Jinshui Xu; Guiju Sun; Shanhu Qiu; Jianan Xu; Haijian Guo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Previous studies have not fully elaborated the association of body mass index (BMI) and metabolic status with cerebrovascular diseases in the older population. Methods and Results Data were sourced from a cross‐sectional study in Jiangsu province of China. A total of 617 755 older adults aged ≥65 years were included in this study. We created body size phenotypes defined by BMI categories and metabolic types. Cerebrovascular diseases were included as an outcome of the study. Logistic regression analysis was used to evaluate the association of BMI and metabolic health status with cerebrovascular diseases. Participants with any metabolic abnormalities were positively associated with cerebrovascular diseases regardless of BMI types (P<0.001). Participants who were underweight (odds ratio [OR], 2.66 [95% CI, 2.32–3.05] in participants with 2 metabolic abnormalities; OR, 3.52 [95% CI, 2.94–4.20] in participants with metabolic syndrome, respectively) had a stronger positive association with cerebrovascular diseases than other BMI types in the same metabolic abnormalities. However, participants with obesity (OR, 1.97 [95% CI, 1.75–2.22] in participants with 2 metabolic abnormalities; OR, 2.81 [95% CI, 2.55–3.11] in participants with metabolic syndrome, respectively) had a weaker positive association with cerebrovascular diseases than other BMI types in the same metabolic abnormalities. These associations were not dependent on sex or age. Conclusions People with any metabolic abnormalities have a stronger positive association with cerebrovascular diseases. Special attention should be given to the potential for cerebrovascular diseases in underweight people when multiple metabolic abnormalities are present (score≥2).